Anti-Sexual Violence Narratives In Islamic Boarding Schools: A Framing Analysis of CNN Indonesia's Youtube Channel - Sumadi, Sumadi; Lilis Nurteti; Arjen Robben GS (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to investigate the ways in which narratives that are anti-sexual violence in Islamic boarding schools are promoted on the YouTube platform by the CNN Indonesia channel. By employing a framing analysis methodology, the purpose of this research is to gain an understanding of the manner in which the media portrays this matter within the framework of the patriarchal social and cultural environment of Indonesia. The findings of the research shed light on seven primary topics, some of which include the centrality of the victims, criticism of the inadequate control of Islamic boarding schools, and the role of the media in pushing societal change. The results of this study demonstrate that the media play a strategic role as agents of social change by means of narratives that support policy reforms and magnify the voices of victims. Regarding the discussion that is taking place regarding the safeguarding of women and children within the framework of religious education, this study is pertinent.